2018
DOI: 10.3390/molecules23040749
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Melatonin Protection from Gastric Mucosal Apoptotic Injury in Experimental Burns

Abstract: Melatonin, a basic secretory pineal gland product, is a nontoxic, multifunctional molecule. It has antioxidant and anti-apoptotic activities and protects tissues from injury. The objective of the present study was to determine the molecular mechanism of melatonin anti-apoptotic effect on gastric injury in a rat burn model. We hypothesized that melatonin gastric protection may be related to the activation of transcription erythroid 2-related factor 2 (Nrf2). Using a 30% total body surface area (TBSA) rat burn m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…This finding is supported by our results showing a reduction in placental gene expression and proteins of pro-inflammatory mediators and oxidative stress markers, 4-HNE. 39 We also observed that A previous study has demonstrated an association between inflammatory markers and thrombotic pathology. 40 Elevated levels of C-reactive protein have been associated with an increased risk of venous thromboembolism, 41 and increased levels of certain pro-inflammatory substances, such as IL-6, have been linked with venous thrombosis.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This finding is supported by our results showing a reduction in placental gene expression and proteins of pro-inflammatory mediators and oxidative stress markers, 4-HNE. 39 We also observed that A previous study has demonstrated an association between inflammatory markers and thrombotic pathology. 40 Elevated levels of C-reactive protein have been associated with an increased risk of venous thromboembolism, 41 and increased levels of certain pro-inflammatory substances, such as IL-6, have been linked with venous thrombosis.…”
Section: Discussionsupporting
confidence: 75%
“…Our study is the first to examine the beneficial effect of antenatal maternally administered melatonin on fetoplacental hemodynamic changes and fetal neuroinflammation caused from IUI‐induced oxidative stress. This finding is supported by our results showing a reduction in placental gene expression and proteins of pro‐inflammatory mediators and oxidative stress markers, 4‐HNE . We also observed that melatonin pretreatment induced an increase in anti‐inflammatory precursor, SIRT1, Nrf2, and HO‐1, suggesting a beneficial neuroprotective effect against an inflammatory insult.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of apoptosis is regulated by apoptosis-related genes, including Bcl-2, Bax, caspase family and Fas membrane proteins, etc. (Hristova et al, 2018) . Bcl-2 is an anti-apoptosis protein and has the function of inhibiting the release of apoptosis factors such as cytochrome C (Negroni et al, 2015) .…”
Section: Discussionmentioning
confidence: 99%
“…The manufacturer's instructions were accurately followed. The ratio of Bax to Bcl-2 was calculated using the formula [29]: …”
Section: Methodsmentioning
confidence: 99%